Atrial-specific reduction of Kir2.1 channel pore diameter in addition to loss of inward-going rectification underlies inducible atrial fibrillation in a mouse model of short QT syndrome type 3. (3rd October 2022) - Moreno-Manuel, A; Macias, A; Cruz, F M; Gutierrez, L; Martinez Carrascoso, I; Bermudez-Jimenez, F J; Vera-Pedrosa, M L; Sanchez-Perez, P; Bernal, J; Jalife, J
Abstract: Introduction: Short QT Syndrome Type 3 (SQTS3) is an extremely rare arrhythmogenic disease caused by gain-of-function mutations in the KCNJ2 gene coding the inward rectifier potassium channel Kir2.1. We investigated arrhythmogenic mechanisms associated with a de-novo mutation (E299V) in Kir2.1 in an 11-year-old boy presenting an extremely abbreviated QT interval, paroxysmal atrial fibrillation, and mild left ventricular dysfunction. Amino acid E299 in the Kir2.1 sequence is necessary for polyamine binding induced inward rectification. Purpose: Test the hypothesis that Kir2.1E299V induces reduced conductance and lack of rectification that causes electrical defects in atrial cardiomyocytes, predisposing patients to atrial arrhythmias. Methods: We used intravenous adeno-associated virus-mediated gene transfer to generate mice expressing wild-type (WT) and the E299V mutant protein. We used ECG, intracardiac stimulation, patch-clamp, molecular biology and computational modelling to characterize the models and study arrhythmia mechanisms in the atria and ventricles. Results: We confirmed WT or mutant Kir2.1 gene expression specifically in the mouse heart. On ECG, the corrected QT (QTc) interval of Kir2.1E299V mice was significantly shorter than Kir2.1WT mice (p<0.0001). The PR interval in Kir2.1E299V was also significantly shorter than WT mice (p<0.0001). On intracardiac stimulation, the largest proportion of arrhythmic events occurred in the atria, as 7 out of 9 Kir2.1E299V mice presented >1 second atrial flutter/fibrillation, while only 2 out of 10 Kir2.1WT mice showed this type of arrhythmia (p=0.023). On patch clamping, both atrial and ventricular cardiomyocytes expressing Kir2.1E299V had extremely abbreviated action potential durations (APD90) at all frequencies studied (p<0.0001). The current/voltage relation of ventricular Kir2.1E299V cardiomyocytes revealed an absence of inward-going rectification and increased IK1 at voltages positive to −80 mV compared to Kir2.1WT cardiomyocytes (p<0.0001). In contrast, while in the atrial Kir2.1E299V cardiomyocytes the outward IK1 was increased at voltages positive to −80 mV with loss of rectification, IK1 was significantly reduced at voltages negative to −80 mV (p<0.0001), suggesting a loss of function leading to atrial arrhythmia inducibility. A higher proportion of Kir2.2 at atrial level and atomic in-silico 3D simulations suggested that the mutation impaired polyamine block of the Kir2.1E299V-Kir2.2 channel while reducing the pore diameter. Conclusions: This first in-vivo mouse model of cardiac-specific SQTS3 recapitulates the electrophysiological phenotype of a patient with the Kir2.1E299V mutation. The mutation results in a Kir2.1 gain-of-function mediated by and absence of rectification. The predominant arrhythmias induced in these SQTS3 mice were supraventricular likely due to the combined lack of inward rectification and atrial-specific reduced pore diameter of the Kir2.1E299V-Kir2.2 channel. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): La Caixa FoundationLa Maratό TV3 Foundation